PENGARUH PENGGUNAAN MODEL PEMBELAJARAN LANGSUNG DAN MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PENCAPAIAN KOMPETENSI MATA PELAJARAN INSTALASI SISTEM OPERASI DASAR DENGAN MENERAPKAN STRATEGI BELAJAR ELABORASI PQ4R DI SMKN 1 SURABAYA - Yektiono, Yektiono (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
The research is: (1).The competency for Students less than 75 %, (2). the lesson to the teacher centre  on that model of learning (3) not yet  teaching with learning strategy to appropriate.This research was to analyze the influence of learning setrategi Use Elaboration PQ4R, Models Direct instructional and the Problem-Based Learning Model (1) Capacity Analysis learners and (2) Skills learners in subjects Base Operating System Installation. This research uses a quasi-experimental with population in this study was the students of class X - TKJ SMK Negeri 1 Surabaya , the sample will be selected using a random selection of the class will be chosen as the experimental class and the class as a class kontrol.Teknik observation, instruments used , namely observation sheet , observation guides , and assessment guide ( in the form of an assessment rubric ) . As for the data collection techniques in the form of a test , a test item . About the test used is a multiple choice questions with five answer choices , and one of them is the answer benar.Teknik Test items include Data Analysis Instruments , Test prasarat Annalisis ( Test of Homogeneity and Normality Test ) also Hypothesis Testing Statistics . The results of this study are differences pencapian competence of learners in analysis capabilities and skills of students in the subjects basic operating system installation due to the Direct Instruction of   and problem -based learning model with the application of learning strategies elaboration PQ4R at SMK 1 Surabaya , obtained results of hypothesis testing in the form of t value and significance when compared with the number of t table. To test the ability of electric circuit analysis obtained t value of 7,605 with sig. 0.000. While   skills acquired to test t value 73,986 with sig. 0.000.Result using of Problem Based Learning  assisted by elaboration PQ4R learning strategy can improve the Ability of Analysing and Installation Skill for Basic Operating System in SMKN 1 Surabaya very significantly.Are Recommanded; (1) to implement models of learning and problem based learning (2) to applicate of learning strategies elaboration PQ4R at SMK Keywords: MPBM, MPL, Elaborasi PQ4R